A new species of Calliostoma (Vetigastropoda: Calliostomatidae) from Canopus Bank, off northeastern Brazil - Cavallari, Daniel C.; Simone, Luiz R.l. (Zootaxa, 2018)
In the present study, Calliostoma melliferum sp. nov. is described from Canopus Bank, a seamount located ~190 km off Fortaleza, Ceará, northeastern Brazil, at depths of 60–260 m. Shell morphology and anatomy of the soft parts are analyzed in detail with the aid of SEM and micro-computed tomography (CT-Scan) techniques. We take the opportunity to provide thorough conchological and anatomical comparisons with similar species from the Southwestern Atlantic.